Hyaluronic acid-polylactic acid copolymer cross-linked gel as well as preparation method and application thereof

By modifying hyaluronic acid and polylactic acid through ion exchange and cross-linking, a stable and biocompatible copolymer gel is formed, addressing mechanical instability and rapid degradation, and enhancing skin regeneration and anti-aging efficacy.

CN119176959AActive Publication Date: 2024-12-24YUNNAN BOTANEE BIO TECH GRP CO LTD +2

Patent Information

Application Number
CN202411299208.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-24
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

Existing hyaluronic acid and polylactic acid-based fillers suffer from poor mechanical stability, rapid degradation, and hydrophobicity issues, leading to adverse immune responses and short maintenance times in anti-aging applications.

Method used

A method involving ion exchange to modify hyaluronic acid and activate polylactic acid for esterification, followed by cross-linking to form a hyaluronic acid-polylactic acid copolymer gel, enhancing stability and hydrophilicity while maintaining biocompatibility.

Benefits of technology

The resulting gel exhibits improved mechanical properties, extended degradation time, and reduced immune response, offering enhanced skin regeneration and anti-aging effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176959A_ABST
    Figure CN119176959A_ABST
Patent Text Reader

Abstract

The invention relates to hyaluronic acid-polylactic acid copolymer cross-linked gel and a preparation method and application thereof.The method comprises the following steps that S1, ions of hyaluronic acid are changed through ion exchange resin, the pH of a solution is adjusted to 7.0 through an alkaline reagent, freeze-drying is conducted, and amphiphilic hyaluronic acid is obtained; s2, activating carboxyl of polylactic acid by using a catalyst to obtain carboxyl-activated polylactic acid; s3, carrying out esterification reaction on the carboxyl-activated polylactic acid and the amphiphilic hyaluronic acid, dialyzing, and freeze-drying to obtain a hyaluronic acid-polylactic acid copolymer; and S4, placing the hyaluronic acid-polylactic acid copolymer in an alkaline solvent, carrying out a cross-linking reaction under the action of a cross-linking agent, and swelling with a PBS buffer solution to obtain the hyaluronic acid-polylactic acid copolymer cross-linked gel. The polylactic acid is grafted to a molecular chain of the hyaluronic acid, so that compared with single hyaluronic acid gel and polylactic acid, not only is the degradation time of cross-linked gel prolonged, but also the hydrophilic performance of the polylactic acid is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of biomaterials, and in particular to a hyaluronic acid-polylactic acid copolymer cross-linked gel and a preparation method and application thereof. Background Art

[0002] Facial aging (such as the appearance of wrinkles, dry skin, and dark pigmentation) is a complex process that is affected not only by internal conditions, such as the breakage of tissue fibers such as collagen and elastin, and the loss of hyaluronic acid and water, but also by external environmental factors, such as air environment, living habits, and bacterial diseases.

[0003] Hyaluronic acid (HA), as a natural biomacromolecule, is composed of D-glucuronic acid and N-acetylamino-D-glucose. It is widely present in various parts of the human body, such as skin, joints, and blood. It has excellent functions such as maintaining moisture, improving skin elasticity, and signal transmission. It is widely used in anti-aging skin products.

[0004] Filling hyaluronic acid is one of the main types of hyaluronic acid products. By injecting hyaluronic acid gel into the dermis of the skin, it can enhance skin elasticity and replenish moisture, thereby improving skin condition. Filling hyaluronic acid has a short operation time and significant effect. It is now a mainstream product in the field of medical beauty filling. However, traditional filling hyaluronic acid gel still has disadvantages such as weak supporting performance, fast degradation rate, and short maintenance time.

[0005] Polylactic acid (PLA) is a biodegradable polymer material approved by the U.S. Food and Drug Administration (FDA) for use in the human body. It is made of lactic acid polymers. In the human body, polylactic acid first decomposes into oligolactic acid, and then further decomposes into lactic acid. By participating in human metabolism, it degrades into carbon dioxide and water and is excreted from the body. When polylactic acid is filled into the human dermis as an injection material, it can stimulate fibroblasts to produce collagen, thereby improving facial volume and achieving the purpose of regeneration and filling. However, polylactic acid has extremely strong hydrophobic properties and is difficult to dissolve in water. Direct injection into the human body will produce an immune response, causing redness, swelling, inflammation and other adverse phenomena.

[0006] Many existing technologies combine hyaluronic acid and polylactic acid to obtain more effective anti-aging filling products.

[0007] CN117085178A discloses an injectable facial filler composition for cosmetic surgery and a preparation method thereof, wherein L-polylactic acid and D-polylactic acid are added to a hyaluronic acid solution, respectively, and the physical interaction between L-polylactic acid and D-polylactic acid is utilized to form a gel by self-crosslinking. Although this method prolongs the degradation time of hyaluronic acid, the gel formed by self-crosslinking has poor stability, weak mechanical properties, and a fast degradation rate.

[0008] CN110964215A discloses a method for preparing a composite gel of L-polylactic acid and cross-linked hyaluronic acid for injection, wherein polylactic acid is added to a hyaluronic acid solution to obtain a freeze-dried substance, and the composite gel is prepared by secondary cross-linking. Since polylactic acid has poor hydrophilicity, this method directly adds polylactic acid to the hyaluronic acid solution, which makes it difficult to disperse evenly in the aqueous solution and is prone to agglomeration, resulting in needle blockage.

[0009] CN117024770A discloses a method for preparing a mixed gel of modified polylactic acid microspheres and sodium hyaluronate. In this method, polylactic acid microspheres are first modified by nicotinamide, and the modified polylactic acid microspheres are then added to a hyaluronic acid solution and mixed to obtain a gel. This method increases the hydrophilicity of polylactic acid to a certain extent, but nicotinamide injected into the body will have an irritating effect on the skin, causing redness, swelling, itching and the like, and the hyaluronic acid solution degrades rapidly in the body and has no obvious filling and shaping effect. Summary of the invention

[0010] The purpose of the present disclosure is to provide a skin anti-aging filler that is stable and highly biosafe.

[0011] To achieve the above object, the present disclosure provides a method for preparing a hyaluronic acid-polylactic acid copolymer cross-linked gel, comprising the following steps:

[0012] S1. Change the ions of hyaluronic acid by ion exchange resin, adjust the solution pH to 7.0 with alkaline reagent, freeze-dry, and obtain amphiphilic hyaluronic acid having the following structure

[0013]

[0014] S2. Activating the carboxyl group of polylactic acid using a catalyst to obtain carboxyl-activated polylactic acid;

[0015] S3. The carboxyl-activated polylactic acid undergoes an esterification reaction with the amphiphilic hyaluronic acid, and after dialysis and freeze-drying, a hyaluronic acid-polylactic acid copolymer having the following structure is obtained.

[0016]

[0017] S4. placing the hyaluronic acid-polylactic acid copolymer in an alkaline solvent to cause a cross-linking reaction under the action of a cross-linking agent, and swelling with a PBS buffer solution to obtain a hyaluronic acid-polylactic acid copolymer cross-linked gel.

[0018] Preferably, the molecular weight of the polylactic acid is 5,000 to 200,000 Da;

[0019] The polylactic acid is selected from one of poly-L-lactic acid, poly-D-lactic acid, racemic polylactic acid or polylactic acid modified with polyethylene glycol.

[0020] Preferably, in the reaction system of step S2, the catalyst includes at least one of N-(3-dimethylaminopropyl)-ethylcarbodiimide, dicyclohexylcarbodiimide, 4-dimethylaminopyridine and N-hydroxysuccinimide, and the solvent used includes dichloromethane or chloroform.

[0021] More preferably, the catalyst is N-hydroxysuccinimide and N-(3-dimethylaminopropyl)-ethylcarbodiimide;

[0022] The mass ratio of the polylactic acid, the N-hydroxysuccinimide and N-(3-dimethylaminopropyl)-ethylcarbodiimide is 1:0.01:0.01 to 1:5:5, the reaction temperature is 25-50°C, and the reaction time is 8-48h.

[0023] Preferably, in the reaction system of step S3, the solvent used includes dimethyl sulfoxide, the mass ratio of the carboxyl-activated polylactic acid to the amphiphilic hyaluronic acid is 1:0.01 to 1:5, the reaction temperature is 40-60°C, the reaction time is 8-24h, and the dialysis time is 2-5 days.

[0024] Preferably, in step S1, the molecular weight of the hyaluronic acid is 20,000 to 2,000,000 Da, the ion exchange resin is a cation exchange resin, the treatment time is 18 to 36 hours, and the alkaline reagent includes a tetrabutylammonium hydroxide solution.

[0025] Preferably, the alkaline reagent comprises a sodium hydroxide solution with a mass fraction of 1%, and the components of the PBS buffer solution are: sodium chloride, disodium hydrogen phosphate and sodium dihydrogen phosphate monohydrate;

[0026] The mass ratio of the hyaluronic acid-polylactic acid copolymer to the cross-linking agent is 1:0.01 to 1:0.5, the cross-linking temperature is 25 to 50°C, the cross-linking time is 12 to 48 hours, and the swelling time is 12 to 72 hours;

[0027] The crosslinking agent includes 1,4-butanediol diglycidyl ether, divinyl sulfone, ethylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether or diethylene glycol diglycidyl ether.

[0028] To achieve the above objectives, the present disclosure also provides a hyaluronic acid-polylactic acid copolymer cross-linked gel, wherein the cross-linked gel is obtained according to any of the preparation methods described above.

[0029] Preferably, the cross-linked gel comprises the following chemical structure:

[0030]

[0031] To achieve the above objectives, the present disclosure also provides a use of the cross-linked gel according to any one of the aforementioned items, wherein the cross-linked gel is used in a facial filler.

[0032] The technical solution claimed in the present disclosure has achieved the following beneficial effects:

[0033] The hyaluronic acid-polylactic acid copolymer cross-linked gel disclosed in the present invention prolongs the degradation time of the cross-linked gel by extending the molecular chain due to the grafting of polylactic acid onto the molecular chain of hyaluronic acid. Compared with a single hyaluronic acid gel, the hyaluronic acid grafted with polylactic acid has a stronger effect of stimulating the regeneration of human collagen. In addition, hyaluronic acid is a natural macromolecule and has no immune response. Polylactic acid is connected to hyaluronic acid by covalent action, which reduces the hydrophobicity of polylactic acid and can be degraded into carbon dioxide and water in the body, with high biological safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present disclosure, the drawings required for describing the embodiments are briefly introduced below.

[0035] Figure 1 The infrared spectra of HA, PLLA and HA-g-PLLA are shown in Figure 1.

[0036] Figure 2 The morphology of the cross-linked gel prepared from HA-g-PLLA. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and beneficial effects of the embodiments of the present disclosure clearer, the technical solution in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.

[0038] Example 1

[0039] This embodiment provides a method for preparing a hyaluronic acid-polylactic acid copolymer cross-linked gel, comprising the following steps:

[0040] S1. Preparation of amphiphilic hyaluronic acid: The ions of sodium hyaluronate are changed by using ion exchange resin, and the pH is adjusted to neutral by using an alkaline reagent. After freeze-drying, amphiphilic hyaluronic acid (HA-TBA) is obtained, and its chemical structure is as follows:

[0041]

[0042] In this step, the molecular weight of sodium hyaluronate is preferably 20,000 to 2,000,000 Da, the ion exchange resin is a cation exchange resin, the treatment time is 18 to 36 hours, and the alkaline agent is a tetrabutylammonium hydroxide solution.

[0043] S2. Activation of carboxyl groups of polylactic acid: dissolve polylactic acid in an organic solvent and add a catalyst to activate the carboxyl groups. The reaction chemical equation is as follows:

[0044]

[0045] In this step, the polylactic acid is poly-L-lactic acid (PLLA), poly-D-lactic acid (PDLA), racemic polylactic acid (PDLLA), polyethylene glycol (PEG)-modified polylactic acid (PLA), including polyethylene glycol-modified L-lactic acid (PLLA-PEG), polyethylene glycol-modified D-lactic acid (PDLA-PEG) and polyethylene glycol-modified racemic polylactic acid (PDLLA-PEG). The molecular weight of the polylactic acid is preferably 5,000 to 200,000 Da, and the organic solvent is dichloromethane or chloroform, preferably dichloromethane;

[0046] The catalyst used in this step is N-(3-dimethylaminopropyl)-ethylcarbodiimide (EDC), dicyclohexylcarbodiimide (DCC), 4-dimethylaminopyridine (DMAP) or N-hydroxysuccinimide (NHS), preferably N-(3-dimethylaminopropyl)-ethylcarbodiimide (EDC) and N-hydroxysuccinimide (NHS). The mass ratio of polylactic acid, EDC and NHS is 1:0.01:0.01 to 1:5:5, the reaction temperature is 25-50°C, and the reaction time is 8-48h.

[0047] S3. Preparation of hyaluronic acid-polylactic acid copolymer: The substances obtained in step S1 and step S2 are blended to prepare a copolymer, which is dialyzed and freeze-dried to obtain a solid copolymer (HA-g-PLA). The reaction process is as follows:

[0048]

[0049] In this step, the mass ratio of hyaluronic acid to polylactic acid is 1:0.01 to 1:5, the blending solvent used is dimethyl sulfoxide (DMSO), the reaction temperature is 40-60°C, the catalyst is diethylamine, the time is 8-24h, and the dialysis time required for the copolymer is 2-5 days.

[0050] S4. Preparation of hyaluronic acid-polylactic acid copolymer cross-linked gel: dissolve the solid copolymer in step S3 in an alkaline solution, add a cross-linking agent, mix well, let stand for cross-linking for 12 to 48 hours, and swell with PBS buffer solution to obtain a hyaluronic acid-polylactic acid copolymer cross-linked gel.

[0051]

[0052]

[0053] In this step, the alkaline solution is a sodium hydroxide solution with a mass fraction of 1%, and the cross-linking agent is one of 1,4-butanediol diglycidyl ether (BDDE), divinyl sulfone, ethylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and diethylene glycol diglycidyl ether, preferably 1,4-butanediol diglycidyl ether;

[0054] In a preferred embodiment, the mass ratio of hyaluronic acid-polylactic acid copolymer to cross-linking agent is 1:0.01 to 1:0.5, the cross-linking temperature is preferably 25-50°C, and the reaction time is preferably 18-36 hours. The components of the PBS buffer solution are sodium chloride, disodium hydrogen phosphate and sodium dihydrogen phosphate monohydrate, and the swelling time is 72 hours.

[0055] The solution in Example 1 is further described in detail below in conjunction with specific application examples.

[0056] Application Example 1

[0057] This application example provides a method for preparing an injectable hyaluronic acid-polylactic acid copolymer cross-linked gel, comprising the following steps:

[0058] S1. Preparation of amphiphilic hyaluronic acid: Weigh 2 g of sodium hyaluronate with a molecular weight of 1,600,000 Da to prepare a hyaluronic acid solution with a concentration of 2%. Soak the sodium hyaluronate solution in a cation exchange resin for 24 hours, adjust the pH of the HA solution to 7.0 with a tetrabutylammonium hydroxide solution, and freeze-dry to obtain an amphiphilic hyaluronic acid solid (HA-TBA);

[0059] S2. Activation of carboxyl groups of polylactic acid: 5 g of poly-L-lactic acid with a molecular weight of 10,000 Da was dissolved in dichloromethane with 191.70 mg of EDC and 115.09 mg of NHS, reacted at 25 ° C for 24 h, and then vacuum dried to obtain polylactic acid (PLLA-NHS) after carboxyl activation;

[0060] S3. Preparation of hyaluronic acid-polylactic acid copolymer: 600 mg of HA-TBA in S1 and 21.6 mg of PLLA-NHS in S2 were weighed and dissolved in dimethyl sulfoxide, and catalyst diethylamine was added. The mixture was reacted at 40° C. for 24 h to obtain a copolymer solution. The copolymer solution was dialyzed for 48 h and then freeze-dried to obtain a freeze-dried sample of hyaluronic acid-polylactic acid copolymer (HA-g-PLLA);

[0061] S4. Preparation of hyaluronic acid-polylactic acid copolymer cross-linked gel: Weigh 500 mg of HA-g-PLLA in S3 and dissolve it in 9.5 mL of 1% sodium hydroxide solution, add 40 μL of 1,4-butanediol diglycidyl ether (BDDE), cross-link at 25°C for 24 hours, add 20 mL of PBS buffer and swell for 72 hours to obtain a cross-linked gel.

[0062] Application Example 2

[0063] This application example provides a method for preparing an injectable hyaluronic acid-polylactic acid copolymer cross-linked gel, comprising the following steps:

[0064] S1. Preparation of amphiphilic hyaluronic acid: Weigh 5 g of sodium hyaluronate with a molecular weight of 1,000,00 Da and dissolve it in water to prepare a hyaluronic acid solution with a concentration of 5%. Soak the sodium hyaluronate solution in ion exchange resin for 24 hours, adjust the pH to 7.0 with tetrabutylammonium hydroxide solution, and freeze-dry the solution to obtain amphiphilic hyaluronic acid (HA-TBA);

[0065] S2. Activation of carboxyl groups of polylactic acid: 5 g of poly (d-lactic acid) with a molecular weight of 10,000 Da was dissolved in dichloromethane with 383.40 mg of EDC and 230.18 mg of NHS, reacted at 25 ° C for 24 h, and then dried in vacuo to obtain carboxyl-activated poly (d-lactic acid) (PDLA-NHS);

[0066] S3. Preparation of hyaluronic acid-polylactic acid copolymer: 600 mg of HA-TBA in S1 and 84 mg of PDLA-NHS in S2 were weighed and dissolved in dimethyl sulfoxide, and catalyst diethylamine was added. The mixture was reacted at 50° C. for 24 h to obtain a copolymer solution. The copolymer solution was dialyzed for 72 h and then freeze-dried to obtain a hyaluronic acid-polylactic acid copolymer;

[0067] S4. Preparation of hyaluronic acid-polylactic acid copolymer cross-linked gel: Weigh 500 mg of the copolymer in S3 and dissolve it in 9.5 mL of 1% sodium hydroxide solution, add 80 μL of 1,4-butanediol diglycidyl ether (BDDE), cross-link at 25°C for 24 hours, and then add 20 mL of PBS buffer for swelling to obtain a cross-linked gel.

[0068] Application Example 3

[0069] This application example provides a method for preparing an injectable hyaluronic acid-polylactic acid copolymer cross-linked gel, comprising the following steps:

[0070] S1. Preparation of amphiphilic hyaluronic acid: Weigh 5 g of sodium hyaluronate with a molecular weight of 1,600,000 Da and dissolve it in water to prepare a 5% hyaluronic acid solution. Soak the sodium hyaluronate solution in ion exchange resin for 24 hours, adjust the pH to 7.0 with tetrabutylammonium hydroxide solution, and freeze-dry the solution to obtain amphiphilic hyaluronic acid (HA-TBA);

[0071] S2. Activation of carboxyl groups of polylactic acid: 5 g of poly-L-lactic acid with a molecular weight of 15,000 Da was dissolved in dichloromethane with 191.70 mg of EDC and 115.09 mg of NHS, reacted at 25 ° C for 24 h, and then dried in vacuo to obtain carboxyl-activated polylactic acid (PLLA-NHS);

[0072] S3. Preparation of hyaluronic acid-polylactic acid copolymer: 1200 mg of HA-TBA in S1 and 102 mg of PLLA-NHS in S2 were weighed and dissolved in dimethyl sulfoxide, reacted at 50° C. for 24 h, and the solution was dialyzed for 72 h and then freeze-dried to obtain a freeze-dried sample of hyaluronic acid-polylactic acid copolymer (HA-g-PLLA);

[0073] S4. Preparation of hyaluronic acid-polylactic acid copolymer cross-linked gel: Weigh 500 mg of HA-g-PLLA in S3 and dissolve it in 4.5 mL of 1% sodium hydroxide solution, add 100 μL of 1,4-butanediol diglycidyl ether (BDDE), cross-link at 25°C for 24 hours, add 20 mL of PBS buffer solution and swell for 72 hours to obtain a cross-linked gel.

[0074] Comparative Example 1

[0075] 500 mg of sodium hyaluronate with a molecular weight of 1,600,000 Da was weighed and dissolved in 9.5 mL of 1% sodium hydroxide solution, and 80 μL of 1,4-butanediol diglycidyl ether (BDDE) was added. After cross-linking at 25° C. for 24 h, 20 mL of PBS buffer was added for swelling to obtain a cross-linked gel.

[0076] Comparative Example 2

[0077] 500 mg of sodium hyaluronate with a molecular weight of 300,000 Da was weighed and dissolved in 9.5 mL of 1% sodium hydroxide solution, 40 μL of 1,4-butanediol diglycidyl ether (BDDE) was added, and after cross-linking at 25° C. for 24 h, 20 mL of PBS buffer was added for swelling to obtain a cross-linked gel.

[0078] Performance comparison

[0079] Using Fourier transform infrared spectrometer at wavelength 4000~400cm -1 Infrared scanning of HA, PLLA and HA-g-PLLA in the corresponding range in Example 1. Please refer to Figure 1 The results showed that the copolymer (HA-g-PLLA) had a peak at 3389 cm -1 (-OH), 1610cm -1 (-COOH), 1378cm -1 (-CH2), 1150cm -1 (COC), 1078cm- 1 (-C=O) etc. all showed characteristic peaks of hyaluronic acid (HA), and compared with pure HA, the copolymer (HA-g-PLLA) showed a peak at 1756 cm -1 、1456cm -1 A new characteristic peak was formed at , which was mainly due to the presence of ester bond (C=O) and methyl group (-CH3) of PLLA, thus confirming that PLLA successfully modified HA. Figure 2 The morphology of the cross-linked gel prepared from this copolymer (HA-g-PLLA) is shown, indicating that this copolymer has gel-forming ability.

[0080] The cross-linked gels in Examples 1 to 3 and Comparative Examples 1 to 2 were subjected to rheological measurements using a rheometer. The results are shown in Table 1. When the amplitude frequency is 10 Hz, the cross-linked gel has a certain filling plasticity effect, and the rheological properties of Examples 1 to 3 are higher than those of the comparative examples.

[0081] Table 1 Rheological properties of Examples 1 to 3 and Comparative Examples 1 to 2

[0082] Elastic modulus / Pa Viscosity modulus / Pa Example 1 33.94 6.34 Example 2 47.93 5.96 Example 3 56.46 9.24 Comparative Example 1 32.35 7.23 Comparative Example 2 10.35 4.52

[0083] The cross-linked gels of Examples 1 to 3 and Comparative Examples 1 to 2 were degraded in vitro using hyaluronidase. The degradation rates are shown in Table 2. The degradation rates of Examples 1 to 3 were lower than those of Comparative Examples 1 to 2, indicating that the polylactic acid group increased the chain length of the hyaluronic acid molecular chain, thereby achieving the purpose of delaying the degradation of the material.

[0084] Table 2 Degradation rate of cross-linked gel of Examples 1 to 3 and Comparative Examples 1 to 2

[0085] 2 days 4 days 6 days Example 1 21.30% 40.30% 63.57% Example 2 15.60% 30.79% 47.19% Example 3 12.02% 21.19% 35.58% Comparative Example 1 19.40% 41.21% 60.17% Comparative Example 2 25.24% 51.24% 72.61%

[0086] The above performance test results show that compared with simple hyaluronic acid cross-linked gel, the hyaluronic acid cross-linked gel grafted with polylactic acid disclosed in the present invention has enhanced mechanical properties and a slowed degradation rate, and can enhance the shaping effect and shaping time when used as an anti-aging filler for the skin.

[0087] The present invention first uses an ion exchange resin to change hyaluronic acid into amphiphilic HA-TBA, and utilizes an amidation reaction to catalyze the carboxyl group of polylactic acid to obtain PLA-NHS, and the activated polylactic acid (PLA-NHS) is grafted and copolymerized with hyaluronic acid (HA-TBA) by an esterification reaction to form a copolymer (HA-g-PLA), and then the copolymer and a cross-linking agent are prepared into a gel under certain conditions. The gel greatly improves the shortcomings of hyaluronic acid, such as poor mechanical properties and short maintenance time in the skin, through the covalent action of polylactic acid and hyaluronic acid. At the same time, polylactic acid is grafted onto hyaluronic acid, which increases the hydrophilicity of polylactic acid and can reduce immune rejection. The cross-linked gel prepared by this method can play the effect of moisturizing, filling and plasticizing, and can stimulate the regeneration of collagen cells in the skin, reduce the generation of wrinkles, and restore skin elasticity.

[0088] The embodiments and application examples described above are merely illustrative descriptions of the present disclosure and are not intended to limit the scope of the present disclosure. Without departing from the design spirit of the present disclosure, various modifications and improvements made to the technical solutions of the present disclosure by ordinary technicians in this field should all fall within the protection scope determined by the present disclosure.

Claims

1. A method for preparing a hyaluronic acid-polylactic acid copolymer cross-linked gel, characterized in that: The following steps are involved: S1. Change the ions of hyaluronic acid by ion exchange resin, adjust the solution pH to 7.0 with alkaline reagent, freeze-dry, and obtain amphiphilic hyaluronic acid having the following structure S2. Activating the carboxyl group of polylactic acid using a catalyst to obtain carboxyl-activated polylactic acid; S3. The carboxyl-activated polylactic acid undergoes an esterification reaction with the amphiphilic hyaluronic acid, and after dialysis and freeze-drying, a hyaluronic acid-polylactic acid copolymer having the following structure is obtained. S4. placing the hyaluronic acid-polylactic acid copolymer in an alkaline solvent to cause a cross-linking reaction under the action of a cross-linking agent, and swelling with a PBS buffer solution to obtain a hyaluronic acid-polylactic acid copolymer cross-linked gel.

2. The preparation method according to claim 1, characterized in that: The molecular weight of the polylactic acid is 5,000 to 200,000 Da; The polylactic acid is selected from one of poly-L-lactic acid, poly-D-lactic acid, racemic polylactic acid or polylactic acid modified with polyethylene glycol.

3. The preparation method according to claim 1 or 2, characterized in that: In the reaction system of step S2, the catalyst includes at least one of N-(3-dimethylaminopropyl)-ethylcarbodiimide, dicyclohexylcarbodiimide, 4-dimethylaminopyridine and N-hydroxysuccinimide, and the solvent used includes dichloromethane or chloroform.

4. The preparation method according to claim 3, characterized in that: The catalyst is N-hydroxysuccinimide and N-(3-dimethylaminopropyl)-ethylcarbodiimide; The mass ratio of the polylactic acid, the N-hydroxysuccinimide and N-(3-dimethylaminopropyl)-ethylcarbodiimide is 1:0.01:0.01 to 1:5:5, the reaction temperature is 25-50°C, and the reaction time is 8-48h.

5. The preparation method according to claim 1 or 2, characterized in that: In the reaction system of step S3, the solvent used includes dimethyl sulfoxide, the mass ratio of the carboxyl-activated polylactic acid to the amphiphilic hyaluronic acid is 1:0.01 to 1:5, the reaction temperature is 40-60°C, the reaction time is 8-24h, and the dialysis time is 2-5 days.

6. The preparation method according to claim 1, characterized in that: In step S1, the molecular weight of the hyaluronic acid is 20,000 to 2,000,000 Da, the ion exchange resin is a cation exchange resin, the treatment time is 18 to 36 hours, and the alkaline reagent includes a tetrabutylammonium hydroxide solution.

7. The preparation method according to claim 1 or 2, characterized in that: In step S4, the alkaline reagent includes a sodium hydroxide solution with a mass fraction of 1%, and the components of the PBS buffer solution are: sodium chloride, disodium hydrogen phosphate and sodium dihydrogen phosphate monohydrate; The mass ratio of the hyaluronic acid-polylactic acid copolymer to the cross-linking agent is 1:0.01 to 1:0.5, the cross-linking temperature is 25 to 50°C, the cross-linking time is 12 to 48 hours, and the swelling time is 12 to 72 hours; The crosslinking agent includes 1,4-butanediol diglycidyl ether, divinyl sulfone, ethylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether or diethylene glycol diglycidyl ether.

8. A hyaluronic acid-polylactic acid copolymer cross-linked gel, characterized in that: The cross-linked gel is obtained according to the preparation method according to any one of claims 1 to 7.

9. The cross-linked gel according to claim 8, characterized in that The cross-linked gel comprises the following chemical structure:

10. Use of the cross-linked gel according to claim 8 or 9, characterized in that: The cross-linked gel is used in facial fillers.

Citation Information

Patent Citations

  • Preparation method of L-polylactic acid and cross-linked hyaluronic acid composite gel for injection, and product obtained by method

    CN110964215A

  • Modified polylactic acid microsphere-hyaluronic acid mixed gel as well as preparation method and application thereof

    CN117024770A

  • Injection type facial filling agent composition for cosmetic and plastic surgery and preparation method of injection type facial filling agent composition

    CN117085178A

  • Cross-linked hyaluronic acid and method for producing the same

    CN101611063A

  • Hyaluronan and biodegradable high polymer modified material and preparation method

    CN102911380A

Cited By

  • Hyaluronic acid-polylactic acid copolymer cross-linked gel, and preparation method therefor and use thereof

    WO2026061423A1